In pursuit of Amitav Ghosh: some recent readings - Tapan Kumar Ghosh (ed.); Prasanta Bhattacharya (ed.) (Hyderabad: Orient Blackswan, 2013)
Contributed articles and some revised version of papers presented at a national seminar held at Tarakeswar Degree College in March 2011.
Keywords: Literature English History; Literature English; Literature